Assessment of Prostate and Bladder Cancer Genomic Biomarkers Using Artificial Intelligence: a Systematic Review - Bazarkin, Andrey; Morozov, Andrey; Androsov, Alexander; Fajkovic, Harun; Rivas, Juan Gomez; Singla, Nirmish; Koroleva, Svetlana; Teoh, Jeremy Yuen-Chun; Zvyagin, Andrei V; Shariat, Shahrokh François; Somani, Bhaskar; Enikeev, Dmitry (Current urology reports, 2024)
PURPOSE OF REVIEW: The aim of the systematic review is to assess AI's capabilities in the genetics of prostate cancer (PCa) and bladder cancer (BCa) to evaluate target groups for such analysis as well as to assess its prospects in daily practice. RECENT FINDINGS: In total, our analysis included 27 articles: 10 articles have reported on PCa and 17 on BCa, respectively. The AI algorithms added clinical value and demonstrated promising results in several fields, including cancer detection, assessment of cancer development risk, risk stratification in terms of survival and relapse, and prediction of response to a specific therapy. Besides clinical applications, genetic analysis aided by the AI shed light on the basic urologic cancer biology. We believe, our results of the AI application to the analysis of PCa, BCa data sets will help to identify new targets for urological cancer therapy. The integration of AI in genomic research for screening and clinical applications will evolve with time to help personalizing chemotherapy, prediction of survival and relapse, aid treatment strategies such as reducing frequency of diagnostic cystoscopies, and clinical decision support, e.g., by predicting immunotherapy response. These factors will ultimately lead to personalized and precision medicine thereby improving patient outcomes.
Keywords: Neoplasm Recurrence, Local; Recurrence; Biomarkers; lidé; mužské pohlaví; umělá inteligence; prostata; Male; Urinary Bladder Neoplasms; recidiva; biologické markery; nádory močového měchýře; Prostate; Artificial Intelligence; lokální recidiva nádoru; Humans